Inhibiting effect of low-molecular weight polyols on the physico-chemical and structural deteriorations of gluten protein during storage of fresh noodles. (30th July 2019) - Ma, Meng; Han, Chuan-Wu; Li, Man; Song, Xiao-Qian; Sun, Qing-Jie; Zhu, Ke-Xue
Highlights: Low-molecular weight polyols improved dough rheological property when properly added. Polyol inhibited noodle texture deterioration although cannot retard microbial growth. Polyols inhibited the collapse of gluten network and deterioration of inner structure. Polyols induced dynamic protein depolymerization and repolymerization during cooking. Abstract: In this study, the inhibiting effects of low-molecular weight polyols on the deterioration of gluten network and noodle texture were systematically investigated, based on dough rheological properties, and the macroscopic, structural and water status changes of gluten protein during storage of fresh noodles. Both glycerol and propylene glycol significantly restrained the decrease of GMP gel weight, LA-SRC value, hardness and springiness, and the increase of cooking loss. SEM showed that polyols retarded the collapse of gluten network, with still continuous gluten fibrils. The inner structure of polyol noodles was much less damaged after 2 days, with more uniform moisture distribution in MRI images. Potential dynamic depolymerization and repolymerization interactions were detected for protein components during processing and cooking, which might contribute to the textural changes. Low-molecular weight polyols inhibited the collapse of gluten network and deterioration of noodle texture although they showed no inhibiting effect on microbial growth.